The physiological implications of absent ductus venosus during fetal and post-natal life - Shweta Bakhru; Nageswara Rao Koneti (Annals of Pediatric Cardiology)
Background: The ductus venosus (DV) is a pivotal component of fetal circulation. Absent DV (ADV) is associated with structural defects, portal vein (PV) anomalies, and chromosomal anomalies. This observational study aims to investigate the impact of ADV on fetal circulation and postnatal outcomes. Materials and Methods: This observational study was conducted from August 2016 to January 2020 at a fetal and pediatric cardiac center. The DV was evaluated as part of routine fetal echocardiography. Cases of ADV were identified. Blood flow and exit points of the umbilical vein were studied. Cardiothoracic ratio, hydrops, and PV were assessed during the initial and follow-up scans. The postnatal evaluation included an ultrasound abdomen and computed tomography with triple-phase imaging to assess portosystemic shunts (PSSs). Serum ammonia levels were monitored. Results: Twelve patients with ADV were identified. The median maternal age and median gestational age were 27.5 years and 22 weeks, respectively. Four patients had intrahepatic drainage, while eight had extrahepatic drainage. All patients (100%) exhibited cardiomegaly, but none developed hydrops. Four patients had persistent PSS postnatally. All four patients with PSS had asymptomatic hyperammonemia. Two patients underwent transcatheter closure of PSS. The intrahepatic variant showed good PV anatomy with no evidence of PSS. Conclusions: DV evaluation should be performed during fetal echocardiography. ADV can lead to cardiomegaly and dilation of the right atrium and ventricle. PSS can be a potential sequela of the extrahepatic variant of ADV.